Design and development of a special service tool for front brake caliper sliding extractor in vehicles - Muhammad Dimas Riantama; Moch Solikin (Universitas Negeri Yogyakarta, 2024)
Special service tools are essential in maintenance and repair processes, aiming to facilitate work. One of the primary maintenance and repair areas in vehicles is the braking system, which requires specialized tools. This study designed and developed a tool to assist with the maintenance and repair of the vehicle brake system. The objectives of this study were to create a sliding calliper extractor for front brakes and to evaluate its performance. The second step involved creating an illustration of the new method and designing the tool. Load testing and design analysis were conducted before production. Design evaluation was necessary before entering the manufacturing stage, and finally, performance testing and evaluation data were collected to ensure conformity with the initial design. The steps resulted in a sliding calliper tool with dimensions of 120 mm x 65 mm x 35 mm, a weight of 0.742 kg, and tensile strength of up to 650 N/65 kg. Testing on the front brake calliper of a Suzuki vehicle demonstrated the tool’s effectiveness in removing calliper pins at a load limit of 650 N. Performance tests confirmed the tool’s functionality and alignment with the initial design. The extractor successfully removed pins with an average load of 500 N/50 kg. The tool was simple and user-friendly, with testing showing no deflection, and no scratches or damage were observed on components around the pin during pin extraction. This result was supported by simulation analysis, where the equivalent stress under a 489 N/49 kg limit load was 47.043 MPa.